Identification of metabolite profile in halal and non-halal broiler chickens using Fourier-Transform Infrared Spectroscopy (FTIR) and Ultra High Performance Liquid Chromatography- Time Of Flight- Mass Spectrometry (UHPLC-TOF-MS) - Nurfatin Syahirah Mohamed Ali; ‘Atiqah Ruqayyah Zabidi; Mohd Nazmi Abd Manap; Shikh Mohd Shahrul Nizan Shikh Zahari; Nazariyah Yahaya (Penerbit Universiti Kebangsaan Malaysia, 2020)
In Malaysia halal meat is fully defined by Jabatan Kemajuan Islam Malaysia (JAKIM) based on the killing method. Halal meat is usually associated with quality as Muslim sought meat from animal killed using Islamic method. In order to ensure the food are meeting the Halal and thoyyiban aspects, the procedure must be monitored along the supply chains beginning from farm to fork. However, there are lack of studies on effect of slaughtering methods on chickens’ metabolite profile. Therefore, metabolomics approach by Fourier-Transform Infrared Spectroscopy (FTIR) And Ultra High Performance Liquid Chromatography- Time of Flight- Mass Spectrometry (UHPLC-TOF-MS) are used in this study to understand the metabolite profile of chickens when subjected to different slaughtering process. The broiler chickens were subjected to Halal (Islamic tradition) and non-Halal slaughtering method (neck poking) where pectoral major muscle tissues from the slaughtered meat were selected for FTIR and UHPLC-TOF-MS analysis. Results from FTIR analysis showed Halal and non-Halal chicken displayed different spectra regardless time of extraction, which was 0 and 24 hours. Spectra obtained from UHPLC-TOF-MS were further analyzed for statistical analysis, which are Principal Component Analysis (PCA) and Partial Least-Squares Discriminant Analysis (PLS-DA) using MetaboAnalyst 4.0. PLS-DA model showed higher intensity of histidine and inosine was recorded in non-Halal chicken while Halal chicken has higher concentration of hypoxanthine. Result from this study indicates that method of slaughter affects the metabolite profile of chicken.